2005
DOI: 10.1089/hum.2005.16.1338
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation and Protection Induced by DNA-hsp65 Vaccination in an Animal Model of Arthritis

Abstract: We described a prophylactic and therapeutic effect of a DNA vaccine encoding the Mycobacterium leprae 65-kDa heat shock protein (DNA-hsp65) in experimental murine tuberculosis. However, high homology of the vaccine to the corresponding mammalian hsp60, together with the CpG motifs in the plasmidial vector, could trigger or exacerbate an autoimmune disease. In the present study, we evaluate the potential of DNA-hsp65 vaccination to induce or modulate arthritis in mice genetically selected for acute inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 52 publications
5
37
0
6
Order By: Relevance
“…32 In our model, there was an increase in IL6 and IL12 splenic-secreting cells in both AIRmax sublines at 20 days of PIA induction (Figure 4). These results corroborate our previous studies, where AIRmax mice produced higher amounts of these proinflammatory cytokines in both ex vivo 14 and in vitro experiments, 33 as compared to AIRmin mice. T cells play an important role in the pathology of this disease.…”
Section: Discussionsupporting
confidence: 93%
“…32 In our model, there was an increase in IL6 and IL12 splenic-secreting cells in both AIRmax sublines at 20 days of PIA induction (Figure 4). These results corroborate our previous studies, where AIRmax mice produced higher amounts of these proinflammatory cytokines in both ex vivo 14 and in vitro experiments, 33 as compared to AIRmin mice. T cells play an important role in the pathology of this disease.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the success of DNAhsp65 immunization in different animal models and the lack of major toxicity detected in either the pre-clinical studies or in a phase I clinical trial (18)(19)(20)(21)(22)(23), it has been suggested that this vaccine could cause necrosis in the lungs of vaccinated animals (24)(25)(26). These results have not been observed by other groups and, on the contrary, several subsequent reports have provided increasing evidence in favour of the potential therapeutic use of Hsp65 against tuberculosis (13)(14)16).…”
mentioning
confidence: 99%
“…The hsp produced by Mycobacterium leprae (hsp65) has been the focus of our group as a DNA vaccine against several pathologies including TB, 27,28 leishmaniasis, 4 diabetes, 6 arthritis, 5 and cancer. 7 For the first time, we are showing in this work the potential role of DNA-hsp65 as an immune modulator of pathology in a helminth infection, using an egg-induced granuloma model.…”
Section: Discussionmentioning
confidence: 99%